Tea Shops in Myanmar: Micro-Institutional Functions for Rural Migrants and Women - Zaw Lin; Joseph J. Molnar (Societies, 2024)
Lahpet-Ye-Hsain, commonly referred to as “tea shops” or teahouses, are versatile establishments that serve as both dining places and social gathering spots. These micro-institutions are fundamental to Myanmar society at the local level, playing a significant role in daily social interactions, economic activities, and political discourse. Operated as private businesses and informal meeting spots, tea shops are primarily staffed by women who serve tea and food to a predominantly male clientele at various times of the day. The size of tea shops can vary, from small snack shops to larger establishments offering a wide range of menu options. In a typical small village tea shop, customers sit on footstools around small square tables, creating a space for sharing tea and food, and exchanging ideas, opinions, problems, hopes, and aspirations. Tea shops attract a diverse range of individuals, as they are known for their inclusive nature that welcomes people from all backgrounds and walks of life, although women are often on the periphery. Historically dominated by men, we suggest that empowering women’s involvement in tea shops could positively impact their agency in other aspects of life, especially during political change. These micro-institutions serve as the initial connection point for residents in the village or neighborhood, traditionally catering to men but now increasingly broadened to women, newcomers, and young individuals exploring new opportunities.